Novel Aspects of Diamond: From Growth to Applications - Yang, Nianjun (Springer, 2016)
This book focuses on new research fields of diamond, from its growth to applications. It covers growth of atomically flat diamond films, properties and applications of diamond nanoparticles, diamond nanoparticles based electrodes and their applications for energy storage and conversion (supercapacitors, CO2 conversion etc.). Diamond for biomimetic interface, all electrochemical devices for in vivo detections and photo-electrochemical degradation of environmental hazards are highlighted.